G.I. baby - Posadas, Francis ([s.l.] Synergy Home Entertainments)
A young woman born of a Filipina mother an American serviceman is forced to survive in the city of lights and temptation which is Angeles. In her journey in the bars and back-alleys she tries to find the father she never knew and herself.
VCD
Story and screenplay by Francis "Jun" Posadas, Erwin T. Lanada, executive producer Angelina Conferido, direcred by Francis "Jun" Posadas, Cesar Aquino
Perla Bautista, Joone Gamboa, Dick Israel, Cherrie Madrigal
Keywords: Drama--Feature.; Feature films